2000
DOI: 10.1021/jm9909443
|View full text |Cite
|
Sign up to set email alerts
|

New Anilinophthalazines as Potent and Orally Well Absorbed Inhibitors of the VEGF Receptor Tyrosine Kinases Useful as Antagonists of Tumor-Driven Angiogenesis

Abstract: The sprouting of new blood vessels, or angiogenesis, is necessary for any solid tumor to grow large enough to cause life-threatening disease. Vascular endothelial growth factor (VEGF) is one of the key promoters of tumor induced angiogenesis. VEGF receptors, the tyrosine kinases Flt-1 and KDR, are expressed on vascular endothelial cells and initiate angiogenesis upon activation by VEGF. 1-Anilino-(4-pyridylmethyl)-phthalazines, such as CGP 79787D (or PTK787 / ZK222584), reversibly inhibit Flt-1 and KDR with IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
171
0
4

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(177 citation statements)
references
References 39 publications
2
171
0
4
Order By: Relevance
“…Imatinib mesylate was extracted from capsules of Gleevec. Vatalanib was prepared according to the published procedure (11). THRX-165724 was prepared by coupling piperazine to the carboxyl group of SU6668 (12).…”
Section: Methodsmentioning
confidence: 99%
“…Imatinib mesylate was extracted from capsules of Gleevec. Vatalanib was prepared according to the published procedure (11). THRX-165724 was prepared by coupling piperazine to the carboxyl group of SU6668 (12).…”
Section: Methodsmentioning
confidence: 99%
“…The in vitro kinase assays were performed in 96-well plates (30 l) at ambient temperature for 15-45 min using the recombinant glutathione S-transferase-fused kinase domains (4 -100 ng, de- pending on specific activity) prepared as described previously (31,46). [␥ 33 P]ATP was used as phosphate donor and polyGluTyr-(4:1) peptide as acceptor.…”
Section: Methodsmentioning
confidence: 99%
“…Assays were optimized for each kinase using the following ATP concentrations: were calculated by linear regression analysis of the percentage inhibition and are averages of at least three determinations. More details of kinase assays can be found elsewhere (31,46).…”
Section: Methodsmentioning
confidence: 99%
“…8,9 In finding new β-methoxyacrylate derivatives, we observed that, phthalazines attached to these pharmacophore were not studied. Phthalazin-1(2H)-one derivatives are of considerable interest due to their antidiabetic, 10 antiallergic, 11 vasorelaxant, 12 PDE4 inhibitor, 13 VEGF (vascular endothelial growth factor) receptor tyrosine kinase (for the treatment of cancer), 14 antiasthmatic, 15 and herbicidal 16 activities. A number of established drug molecules like Hydralazine, 17,18 Budralazine, 19,20 Azelastine, 21,22 Ponalrestat, 23 and Zopolrestat, 24 were prepared from the corresponding phthalazinones.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 In finding new β-methoxyacrylate derivatives, we observed that, phthalazines attached to these pharmacophore were not studied. Phthalazin-1(2H)-one derivatives are of considerable interest due to their antidiabetic, 10 antiallergic, 11 vasorelaxant, 12 PDE4 inhibitor, 13 VEGF (vascular endothelial growth factor) receptor tyrosine kinase (for the treatment of cancer), 14 The diverse biological activities of β-methoxyacrylate, phthalazin-1(2H)-one, and isoxazoline pharmacophores envisaged us to plan a new lead compounds that may exhibit wide pharmacological activities. By combining these pharmacophore components in a molecule to give a compact system, we designed and synthesized a series of phthalazin-1(2H)-one derivatives containing β-methoxyacrylate and isoxazoline moieties.…”
mentioning
confidence: 99%